Computer technology in construction proceedings of a conference organized by the Institution of Civil Engineers, and held in London on 25-27 September, 1984. (Thomas Telford, 1985)
Written for civil engineers, these papers on computer technology in construction focus on the structure of the industry, the growing complexity of design and construction, provide information management, and guidelines for evaluation, and conclude with advances and applications.